The equation given is \(-2x + 3x - 1 = -2\). First, we simplify it:
Combine like terms: \[ (-2x + 3x) - 1 = -2 \] This simplifies to: \[ x - 1 = -2 \]
Next, we isolate \(x\): \[ x = -2 + 1 \] \[ x = -1 \]
Since this is a linear equation, we do not need to use the quadratic formula. The solution is \(x = -1\).
If there were a quadratic term in the equation, you would use the quadratic formula. However, as it stands, the solution is simply:
\[ x = -1 \]
If you need a different type of problem or if there was a part of the problem missing (such as a quadratic equation), please clarify!